Promoting Seed Germination of Some Plant Species by Rhamnolipid Produced by Pseudomonas aeruginosa - Zeena Ghazi Faisal (Scientifica)
With growing environmental concerns and a growing world population, there is an interest in developing cheap, efficient, and environmentally friendly substances that benefit humanity. Microbial surfactants are nontoxic, biodegradable bioproducts that provide sustainable solutions in agricultural applications due to their many benefits over their synthetic counterparts. Hence the crucial importance of scientific research to understand the effect of microbial surfactants on plant development. The present study aimed to assess the effect of rhamnolipid produced by Pseudomonas aeruginosa on seed germination of wheat (Triticum aestivum), barley (Hordeum vulgare), okra (Abelmoschus esculentus), onion (Allium cepa), and lettuce (Lactuca sativa) under laboratory conditions. The results showed that P. aeruginosa was capable of producing 3.83 g/L of viscous, honey-colored rhamnolipid, which was capable of lowering the surface tension to 30 ± 0.33 mN/m. Different concentrations of rhamnolipid ranging from 0.25 to 1.00 g/L were assessed, with distilled water acting as a control. After treatment of seeds, results showed that applying 0.25 g/L of rhamnolipid can significantly increase seed germination to 100% on the fourth day of sowing okra and lettuce, and on the fifth day of sowing onion seeds, compared to control groups that recorded 60%, 50%, and 55%, respectively. In wheat and barley seeds, applying rhamnolipid can protect seeds from pathogenic fungi while delaying their germination to 60% and 70% on the third day of sowing, while 90% and 100% have been reported in the control groups. Thus, this biological molecule demonstrates promising results in enhancing seed germination of the studied species by protecting them from phytopathogens and then aiding plant growth.